Observing Near-Earth Objects with the James Webb Space Telescope. (4th January 2016) - Thomas, Cristina A.; Abell, Paul; Castillo-Rogez, Julie; Moskovitz, Nicholas; Mueller, Michael; Reddy, Vishnu; Rivkin, Andrew; Ryan, Erin; Stansberry, John
Abstract: The James Webb Space Telescope ( JWST ) has the potential to enhance our understanding of near-Earth objects (NEOs). We present results of investigations into the observability of NEOs given the nominal observing requirements of JWST on elongation (85°–135°) and non-sidereal rates (<30 mas s −1 ). We find that approximately 75% of NEOs can be observed in a given year. However, observers will need to wait for appropriate observing windows. We find that JWST can easily execute photometric observations of meter-sized NEOs that will enhance our understanding of the small NEO population.